Development of a prototype kitchen cutting equipment / Mukhriz Azizi and Zeno Michael - Azizi, Mukhriz; Michael, Zeno (School of Mechanical Engineering, 2023)
In the ever-evolving landscape of household equipment driven by globalization, traditional tools are being replaced by technologically advanced appliances. The Vorwerk Thermomix has gained popularity for its ability to simplify cooking processes, but its high cost renders it inaccessible for many households, leaving individuals to rely on conventional tools like kitchen knives and cutting boards. However, these tools pose safety risks, particularly when time is limited, leading to potential injuries and hazards. To address this challenge, this project proposes the development of an affordable and safe kitchen cutting machine. Constructed using durable materials such as stainless steel, glass, and springs, the machine will utilize a cutting method similar to a paper cutter, ensuring convenience, durability, and user safety to provide a seamless cooking experience. Extensive research and development is conducted to identify appropriate materials, machinery, and equipment, followed by rigorous testing to ensure efficiency, effectiveness, and safety, tailored to meet the specific needs of households. By introducing an affordable and safe kitchen cutting machine, this project aims to reduce the risk of injuries, enhance safety and efficiency in cooking, and empower users to enjoy a superior culinary experience